(untitled) (Research, Society and Development, 2022)
The clinical and anatomopathological findings of a case of granulomatous dermatitis by Halicephalobus gingivalis in a horse in northeastern Brazil, are described. The animal presented multifocal, non-pruritic and painless cutaneous nodules, predominantly arranged in the abdominal, thoracic, cervical and facial regions, and on the lateral surface of the thoracic and pelvic limbs. Skin fragments were collected, fixed in 10% buffered formalin, cleaved, routinely processed for histopathology and sent for anatomopathological evaluation. Macroscopically, well-delimited exophytic nodules with an alopecic, multilobulated and crusted surface, measuring 0.5 to 1 cm in diameter, were observed. When cut, the nodules were soft, with a yellowish, compact and smooth surface. Histopathology revealed a focally extensive, accentuated nodular and granulomatous dermatitis associated with rhabditiform nematode parasites, morphologically compatible with H. gingivalis. H. gingivalis infections should be included in the differential diagnosis of granulomatous dermatitis in horses. Treatment with ivermectin associated with surgical excision of the nodules proved to be efficient.